"Being Unfilial Condemns You to Hell": Integrative Treatment for Social Anxiety Shaped by Domestic Abuse, Confucian Values, and Taoist Beliefs. (April 2019) - Lau, Karen Chi-Kwan; Sündermann, Oliver
Social anxiety is a common and treatable condition but less is known about how to adapt evidence-based approaches in a culture-sensitive way to Asian clients. We present the case of "Sally, " a 25-year-old Chinese Singaporean female who suffered from severe and long-standing social anxiety disorder (SAD), and secondary low mood. Contributing factors included a history of domestic abuse, as well as culturally influenced authoritarian parenting emphasizing the Confucian value of filial piety and reinforced by Taoist beliefs of karmic retribution and supernatural punishment. Treatment was based on Clark and Wells's cognitive model of SAD with a focus on behavioral experiments, and was enhanced using a schema mode formulation and imagery rescripting to address relevant early memories that were at the origin of the social anxiety. Sally received a total of 42 sessions over the course of 21 weeks, during which she made steady progress toward recovery. Her self-reported depression and social phobia fell from the "severe clinical" range pretreatment to the "non-clinical" range posttreatment; these gains were maintained at 6 months follow-up. Sally's functioning fully recovered, and she returned to work and school. While behavioral experiments for dropping safety behaviors were useful for overcoming the social anxiety, schema formulation was important for providing Sally with insight to her thought process, and imagery rescripting was crucial for weakening her self-criticism and internalized black and white thinking on filial piety. The significance of culture and religion in SAD, and the potential of adapting cognitive therapy in a culture-sensitive way is discussed.